A Recent Quest for Religious Roots: The Revival of the Guangze Zunwang Cult and Its Sino-Southeast Asian Networks, 1978-2009 - Chia, Jack Meng-Tat (Journal of Chinese religions, 2013)
This article examines issues surrounding the revival of the cult of Guangze Zunwang and its religious networks between Southeast China and the Chinese in Malaysia and Singapore from 1978 to 2009. It reveals that the quest of overseas Chinese for the religious roots of Guangze Zunwang's cult has contributed to the rebuilding of the Shishan Fengshan Si in particular and the cult's sacred sites in general. The resurgence of diasporic religious networks has facilitated the transnational movement of financial resources and allowed overseas Chinese to make regular pilgrimages and participate in the cult's religious activities in China. I argue that, on the one hand, this renewal of religious ties, which has led to the proliferation of pilgrimages and religious excursions to the cult's sacred sites in China, and expeditions from China to Malaysia and Singapore, has benefited both the Shishan Fengshan Si and the overseas temples; on the other hand, it led to religious competition and inter-temple rivalries between the different principal sites of the cult in China.